Morphometric Variations Between Triploid and Diploid Clarias gariepinus (Burchell, 1822) - Normala Jalil; Mohd Azizul Alim; Abol Munafi Ambok Bolong; Nur Asma Ariffin; Khor Waiho; Okomoda T. Victor; Shahreza Md Sheriff (Croatian Journal of Fisheries, 2017)
Several scientific methods have been described in the identification of triploid fish. However, many of these methods are not applicable for routine management purposes due to their complexity and cost. In this study, the possibility of using morphological variation as a least cost and less complex method of distinguishing triploid and diploid African catfish Clarias gariepinus (Burchell, 1822) was examined. Triploid catfish were produced by cold shock of fertilized eggs in 5°C for 20 mins (at approximately 3 mins after fertilization). The fish were incubated, hatched and raised for 3 months. Ploidy levels of the fish were then ascertained by observing the erythrocyte shape. Triploid erythrocyte was ellipsoidal in shape while diploid was round. Morphological characterization was then carried out on 100 samples each of triploid and diploid African catfish. Although significant differences were observed in many parameters, the principal morphometric difference between triploid and diploid African catfish could not be clearly distinguished. It was therefore concluded that morphological characteristics is not ideal for discriminating triploids and diploids of African catfish. The used of erythrocyte characteristics still remains the cheapest and relatively effective method for triploid and diploid determination in African catfish.